Species Identification and Fungicide Sensitivity of Fusarium spp. Causing Peanut Root Rot in Henan, China - Min Li; Liting Chen; Qinqin Wang; Leiming He; Yun Duan; Xuewei Mao; Lin Zhou (Journal of Fungi, 2025)
Peanut Root Rot (PRR) is a devastating disease that significantly limits peanut production worldwide. Although PRR has been frequently reported in Henan Province of China, the predominant Fusarium species and their sensitivity to different fungicides remain unclear. Between 2021 and 2023, we surveyed 81 peanut fields across 17 cities in Henan Province, China, to assess PRR prevalence and Fusarium species distribution. A total of 1131 Fusarium isolates were identified based on the morphological characters and phylogenetic analyses and classified into 11 recognized Fusarium species: F. solani (56.06%), F. oxysporum (20.87%), F. neocosmosporiellum (13.62%), F. proliferatum (4.69%), F. acuminatum (1.33%), F. commune (1.15%), F. graminearum (1.06%), F. pseudograminearum (0.35%), F. ipomoeae (0.35%), F. lacertarum (0.26%), and F. armeniacum (0.26%). Pathogenicity assessments showed that all 11 Fusarium species were capable of causing PRR, with F. solani exhibiting the highest isolation frequency and widespread distribution in all areas. Furthermore, the four Fusarium species (F. solani, F. oxysporum, F. neocosmosporiellum, and F. proliferatum) were highly sensitive to the six fungicides, including prochloraz (EC50 values of 0.02 ± 0.00~0.06 ± 0.01 mg/L), pydiflumetofen (EC50 values of 0.31 ± 0.07~0.67 ± 0.06 mg/L), tetramycin (EC50 values of 0.11 ± 0.02~0.58 ± 0.08 mg/L), tebuconazole (EC50 values of 0.26 ± 0.07~0.65 ± 0.10 mg/L), prothioconazole (EC50 values of 1.14 ± 0.16~3.15 ± 0.81 mg/L), and difenoconazole (EC50 values of 0.62 ± 0.12~3.58 ± 0.76 mg/L). This comprehensive study is the first systematic documentation on the prevalence, virulence, and fungicide sensitivity of PRR pathogens in Henan Province. The findings of the current study will provide a theoretical basis for the effective management of peanut root rot in Henan, China.